2003
DOI: 10.1155/np.2003.129
|View full text |Cite
|
Sign up to set email alerts
|

Clumsiness and Disturbed Cerebellar Development: Insights From Animal Experiments

Abstract: Cerebellar functioning has been implied in the fine adjustments of muscle tone, in the coordination and the feed-forward control of movements and posture, as well as in the establishment and performance of motor skills. The cerebellar cortex in mammals develops late in neuro-ontogeny and an extrapolation from experimental results indicates that in the human the proliferation of the granule cells and the development of circuitry in the cerebellar cortex starts only in the last trimester of pregnancy and lasts u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 52 publications
(55 reference statements)
2
28
0
Order By: Relevance
“…In the current study, three out of ten children who did not show differences in the circle drawing appeared to have limited timing deficits in the discontinuous line drawing. We argue that this restricted timing problem implicates a cerebellar 'explicit timing' impairment, as suggested by other studies, indicating a possible link between compromised cerebellar function and the timing problems in both animal studies [7] and human experiments [10].…”
Section: Nih Public Accesssupporting
confidence: 73%
See 1 more Smart Citation
“…In the current study, three out of ten children who did not show differences in the circle drawing appeared to have limited timing deficits in the discontinuous line drawing. We argue that this restricted timing problem implicates a cerebellar 'explicit timing' impairment, as suggested by other studies, indicating a possible link between compromised cerebellar function and the timing problems in both animal studies [7] and human experiments [10].…”
Section: Nih Public Accesssupporting
confidence: 73%
“…In the current study, three out of ten children who did not show differences in the circle drawing appeared to have limited timing deficits in the discontinuous line drawing. We argue that this restricted timing problem implicates a cerebellar 'explicit timing' impairment, as suggested by other studies, indicating a possible link between compromised cerebellar function and the timing problems in both animal studies [7] and human experiments [10].In summary, our findings support the notion of a compromised "explicit timing" (higher variability in discontinuous movements), or a compromised "dynamic control" (higher variability in drawing circles) or both (higher variability in drawing discontinuous lines but not circles). The heterogeneous nature of the DCD population is further confirmed by individual analysis.…”
supporting
confidence: 78%
“…This period results of a number of events including: neuronal and glial proliferation, outgrowth of axons and dendrites, establishment of synaptical contacts, as well as myelination (Altman & Bayer, 1997). This late development makes the cerebellum a structure particularly vulnerable to insufficient supply of nutrients or to side and possible beneficial effects of pharmacological treatments (Gramsbergen, 2003). It has been shown that a restriction of daily food intake to dams delays the motor development and behavior associated with a disturbed cerebellar development of the offspring (Gramsbergen, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This late development makes the cerebellum a structure particularly vulnerable to insufficient supply of nutrients or to side and possible beneficial effects of pharmacological treatments (Gramsbergen, 2003). It has been shown that a restriction of daily food intake to dams delays the motor development and behavior associated with a disturbed cerebellar development of the offspring (Gramsbergen, 2003). On the other hand, Collucia et al (2009) showed that omega-3 supplementation during gestation and lactation improved motor coordination in juvenile-adults rats.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern is not inconsistent with the fetal programming and DOHaD theories, as it is possible that the affected area of gross motor development had not manifested at the earlier time point, or was not readily measurable (Glover, 2014b). It is possible that disruptions to the development of the basal ganglia underlie deficits in gross motor skills (Gabbard, 2012), and because the brain continues to develop past the first year of life, deficits may not become evident until this process is complete (Gramsbergen, 2003). This may explain why some of our effects only emerged at 30 months, but measurement at future time points would be necessary to determine whether these new effects continue.…”
Section: Prenatal Maternal Stress and Child Motor Developmentmentioning
confidence: 74%